How a Company's Physical Work Environment, Leadership Style, and Employee Motivation Affect Job Satisfaction and Performance - I Made Adnyana; Elfida Veronica; Rumainur (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
The primary aim of this research is to investigate the impact of the physical work environment, leadership, and work motivation on employee job satisfaction, and subsequently, how this affects staff performance at PT. Graha Prima Electrical Ambassador in Jakarta. The physical work environment, leadership, and job motivation are significant factors in an organisational setting that can have a considerable influence on the well-being and performance of employees. The current investigation will utilise quantitative research approaches. The study sample encompasses the entirety of the population, which is composed of a total of 35 employees. Nevertheless, the scope of the sample is restricted to those who are directly engaged in marketing activities, with the intention of enhancing the research results. The study's results suggest that there exists a strong and positive correlation between several aspects, such as the physical work environment, leadership, and work motivation, and the level of job satisfaction experienced by employees. The three independent factors have a substantial influence on the dependent variable, explaining 51.3% of its variability. The present study provides evidence that job satisfaction at PT Duta Listrik Graha Prima in Jakarta is influenced by various elements, including physical work environment characteristics, leadership style, and work motivation. These factors, in turn, have an impact on employee performance.